Aktivitas Kombinasi Ekstrak Etanol Daun Kersen (Muntingia calabura L.) dan Kloramfenikol Terhadap Salmonella typhi - Maharani, Shafira Arifah; Munawaroh, Rima (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Typhoid fever, caused by Salmonella typhi, remains a significant health burden. Chloramphenicol is a first-line antibiotic for its treatment; however, increasing bacterial resistance necessitates alternative therapeutic strategies. Combining antibiotics with natural compounds is a potential approach to overcome resistance and reduce antibiotic doses. Kersen leaves (Muntingia calabura L.) have been reported to contain bioactive compounds with antibacterial properties. Objective: This study aimed to evaluate the in vitro interaction between ethanolic extract of kersen leaves and chloramphenicol against Salmonella typhi using the checkerboard assay method. Methods: The ethanolic extract was obtained through maceration. Phytochemical constituents were analyzed qualitatively using tube tests and Thin-Layer Chromatography (TLC) with silica gel GF254 as the stationary phase and a chloroform:methanol (8:2 v/v) mobile phase. The antibacterial activity, expressed as Minimum Inhibitory Concentration (MIC), was determined for both the single extract and chloramphenicol using the microdilution method with resazurin indicator. The interaction between the two agents was assessed using the checkerboard assay, and the Fractional Inhibitory Concentration Index (FICI) was calculated. Results: Phytochemical screening revealed that the ethanolic extract of kersen leaves contained alkaloids, steroids, flavonoids, tannins, and saponins. The MIC value of chloramphenicol alone was 19.5 µg/mL, while the extract alone showed an MIC of >1000 µg/mL against S. typhi. The checkerboard assay results indicated an increase in the MIC of chloramphenicol in combination with the extract; however, the FICI value could not be definitively determined due to the inability to establish the extract's MIC in the combination. Conclusion: The ethanolic extract of kersen leaves contains various secondary metabolite groups. While chloramphenicol exhibited antibacterial activity, the extract alone did not show inhibitory activity at the tested concentrations. The combination test suggested a potential alteration in the effectiveness of chloramphenicol, but the interaction type (synergistic, additive, indifferent, or antagonistic) could not be conclusively classified. Further investigation using fractionated or isolated compounds from the leaves is recommended.